IMPLEMENTASI METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH MENENGAH ATAS NEGERI (SMA) 11 BANDUNG - Lisa Diyah Ma'rifataini (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2018)
AbstractThe Ministry of Religious Affairs in cooperation with ACDP has facilitated 40 PAI teachers to attend a training of Islamic Religious Education learning methods in Oxford, English. Among the learning methods implemented in Oxford are Market Place Activites, Expert Group, and Group Investigation methods. Such learning methods are not yet familiar to PAI teachers in Indonesia, so then a question arises as to how the implementation of such PAI methods after the said training. This research deployed experimental method. The results showed that the Market Place Activities, Expert Group, and Group Investigation learning methods had been implemented by PAI Teachers of SMAN 11 of Bandung upon their PAI learning activities; The students responded positively to those three implemented methods, according to the students, the learning materials taught through Market Place Activities method make them easily to understand, so did they when taught through Expert Group and Group Investigation. The result of significant test of those three methods is 0,008, it shows that these three methods, based on the students’ achievement on pre-test and post-test, improved and there was no difference between these three learning methods. Supporting factors in the application of these three methods are the teachers’ masteries thereof, the students accustomed to receive learning materials through application of various learning methods, the school management encourages each teacher to develop various learning methods, the school’s infrastructures, and the supporting learning resources and learning media in implementing such learning methods.Abstrak Kementerian Agama bekerjasama dengan ACDP telah memberikan fasilitas 40 guru pendidikan agama Islam mengikuti pelatihan metode pembelajaran PAI di Oxford Inggris. Diantara metode pembelajaran yang diimplementasikan di Oxford adalah metode Market Place Activites, Expert Group, dan Group Investigation. Metode-metode pembelajaran tersebut masih belum familliar dikalangan guru PAI di Indonesia, sehingga timbul pertanyaan bagaimana implementasi tiga metode PAI pasca pelatihan. Penelitian ini menggunakan metode eksperimen. Hasil penelitian menunjukkan metode Market Place Activities, Expert Group, dan Group Investigation pada pembelajaran PAI telah diimplementasikan oleh Guru PAI SMA Negeri 11 Bandung; Respon siswa terhadap tiga metode mengatakan baik, materi dengan metode Market Place Actifitties pada umumnya siswa mengatakan sangat mudah, Expet Group dan Group Invergation siswa mengatakan mudah. Hasil uji signifikansi dari tiga metode tersebut sebesar 0,008, ini menunjukkan ketiga metode berdasarkan hasil pre tes dan post tes prestasi siswa meningkat dan tidak ada perbedaan diantara ketiga metode pembelajaran tersebut. Faktor pendukung dalam penerapan ketiga metode tersebut adalah Guru menguasai metode pembelajaran, siswa terbiasa menerima pembelajaran melalui penerapan berbagai metode pembelajaran, manajemen sekolah mendorong setiap guru untuk mengembangkan berbagai  metode pembelajaran, sarana prasarana, sumber belajar dan media pembelajaran mendukung dalam mengimplementasikan metode pembelajaran tersebut.